Describing heat dissipation in the resistive state of three-dimensional superconductors - Cadorim, Leonardo Rodrigues [UNESP]; de Toledo, Lucas Veneziani [UNESP]; Sardella, Edson [UNESP] (Elsevier, 2024)
In this work we study the role of the heat diffusion equation in simulating the resistive state of superconducting films. By analyzing the current–voltage and current-resistance characteristic curves for temperatures close to Tc and various heat removal scenarios, we demonstrate that heat diffusion notably influences the behavior of the resistive state, specially near the transition to the normal state, where heat significantly changes the critical current and the calculated resistance. Furthermore, we show how the efficiency of the substrate has important effects in the dynamics of the system, particularly for lower temperatures. Finally, we investigate the hysteresis loops, the role of the film thickness and of the Ginzburg–Landau parameter, the findings reassuring the significance of accounting for heat diffusion in accurately modeling the resistive state of superconducting films and provide valuable insights into its complex dynamics. To accomplish these findings, we have used the 3D generalized Ginzburg–Landau equation coupled with the heat diffusion equation.
Keywords: Heat dissipation; Three dimensional superconductor; Vortex–antivortex dynamics